Partnering for progress : Boston University, the Chelsea Public Schools, and urban education reform - Candal, Cara Stillings (Emerald Publishing Limited : IAP, 2009)
For decades, education researchers have understood that school/university partnerships can be beneficial for education reform. K-12 institutions derive benefits from working with professors and university students, and higher education institutions use local schools as sites for teacher training and school improvement research. Partnerships between universities and entire school districts for the explicit purpose of school district turnaround are extremely rare, however. This is one reason why the longstanding partnership between Boston University and the Chelsea Public School District is truly one of a kind. In 1989 Boston University committed itself to the day to day management of Chelsea's schools, which were beleaguered with financial, managerial, and social problems. After twenty years and in large part thanks to that Partnership, the Chelsea Public Schools, once the lowest performing in Massachusetts, have become some of the state's highest performing urban schools.In this collection, scholars from Boston University, the Chelsea Public schools, and abroad examine the history the Boston University/Chelsea Public Schools Partnership and the important changes that are now a part of its legacy. Contributors examine both some of the promises fulfilled and some of the pitfalls encountered along the way, and they do so with an eye to how the Boston University/Chelsea experience can inform other school districts and universities interested in forging partnerships. How does a university take fiscal and managerial responsibility for a struggling school district and what are the challenges inherent to such a unique relationship? What specific resources can a university bring to a struggling school district and how does a school district in turn contribute to the betterment of the university? Also, how does a longstanding partnership survive and thrive in the midst of a dynamic federal and state education reform climate?The lessons outlined in this volume should be informative for researchers, policy makers, and school and university leaders interested in the possibilities that school/university partnerships hold for true education reform.
Keywords: Chelsea Public Schools.; Boston University.; Education, Urban -- Massachusetts -- Chelsea -- Case studies.; Educational change -- Massachusetts -- Chelsea -- Case studies.; College-school cooperation -- Massachusetts -- Chelsea -- Case studies.; elektronické knihy; Case studies.; Education -- Urban.; Educational strategies and policy.; Education.; Urban communities.; electronic books